Output stream of a binding neuron - Vidybida, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
For a binding neuron with threshold 2 stimulated by a Poisson stream, we determine the intensity of the output stream and the probability density for the lengths of the output interpulse intervals. For threshold 3, we determine the intensity of the output stream.